Assessing Habitat Suitability for the Invasive Species Lantana camara on Bali Island: A Model Using the Biodiversity and Climate Change Virtual Laboratory (BCCVL) - Iryadi, Rajif; Sutomo; Saputra, Muhammad Hadi; Humaida, Nida; Pujiono, Eko; Sukmawati, Jalma Giring; Hani, Aditya; Swari, Komang Kartika Indi; Sari, Dewa Ayu Intan; Atmaja, Muhammad Bima; Herningtyas, Wieke; Wahyuningtyas, Reni Setyo; van Etten, Eddie (Institut Pertanian Bogor (IPB University), 2024)
Indonesia, known for its high biodiversity, is threatened due to alien plants that invade local plant species in forest areas. West Bali National Park is overgrown with invasive exotic plants, such as Lantana camara L., known locally as the kembang telek. The research aims to predict the distribution of L. camara using species distribution models (SDMs) and analysis variable contribution in the model featured in the biodiversity climate change virtual laboratory (BCCVL) application. L. camara distribution prediction model in Bali used the Bioclim data input by identifying areas of low, medium, and high habitat suitability. Central mountainous regions, including parts of Buleleng, Jembrana, Bangli, Karangasem, and Tabanan, show the highest suitability. Response curves demonstrated the correlation between climate variables and occurrence probability, highlighting the specific condition of rainfall and temperature ranges favoring Lantana's growth. The model showed a reliable AUC value of 0.89, indicating realibility. Potential improvements through additional environmental parameters were suggested. While L. camara has some potential benefits as a medicinal plant in Balinese culture, its invasive nature poses significant threats to native ecosystems. The predictive map offers valuable insights for authorities to implement initiative-taking strategies for preventing and controlling Lantanas spread in vulnerable areas of Bali.